1997
DOI: 10.1111/j.1553-2712.1997.tb03761.x
|View full text |Cite
|
Sign up to set email alerts
|

New‐onset Bronchospasm or Recrudescence of Asthma Associated with Cocaine Abuse

Abstract: Objective: To determine whether the occurrence of new-onset bronchospasm or the recrudescence of asthma is associated with the use of cocaine. Methods: A consecutive sample of patients presenting to an inner-city adult ED with new-onset bronchospasm or recrudescence of bronchospasm after >5 years were prospectively enrolled in a case-control prevalence study. The bronchospasm patients were queried as to their exposure to illicit drugs, and urine was obtained to screen for cocaine and its metabolite, benzoylecg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
5

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 11 publications
0
11
0
5
Order By: Relevance
“…Several studies have shown that patients who abuse drugs may be at increased risk of severe asthma exacerbations or asthma death. 14,15,19,20,48 Baxter et al 72 demonstrated that patients with substance-related disorders and persistent asthma fill prescriptions for controller medications at lower rates than patients without substance-related disorders. Although the authors cannot say whether these differences are due to differential access to care, decreased compliance with treatment recommendations, or the receipt of substandard care, these findings still may partially explain the disparities in asthma outcomes observed for these patients.…”
Section: Asthma Care In Patients With Substance Abuse Disordersmentioning
confidence: 98%
See 3 more Smart Citations
“…Several studies have shown that patients who abuse drugs may be at increased risk of severe asthma exacerbations or asthma death. 14,15,19,20,48 Baxter et al 72 demonstrated that patients with substance-related disorders and persistent asthma fill prescriptions for controller medications at lower rates than patients without substance-related disorders. Although the authors cannot say whether these differences are due to differential access to care, decreased compliance with treatment recommendations, or the receipt of substandard care, these findings still may partially explain the disparities in asthma outcomes observed for these patients.…”
Section: Asthma Care In Patients With Substance Abuse Disordersmentioning
confidence: 98%
“…Several studies reported a relatively high prevalence of cocaine use among patients with asthma exacerbation that possibly contributes to the increase in asthma morbidity. 15,16,19 Levine et al 16 reported a 42.8% prevalence rate of cocaine or heroin use among adult patients who had been admitted to an inner-city Chicago hospital for acute asthma exacerbations. They also found that cocaine use was associated with higher intubation rates and with longer lengths of stay and a higher likelihood of being admitted to the intensive care unit.…”
Section: Cocaine and Asthmamentioning
confidence: 98%
See 2 more Smart Citations
“…This observation has also been supported by anecdotal evidence from clinical colleagues, although there is little published research in this area. 6 Previous studies have reported an association between drug misuse and asthma exacerbations [7][8][9][10] and respiratory disease and lower quality of asthma care among drug misusers. 11 Other previous studies also suggest a possible association between asthma mortality and drug misuse.…”
mentioning
confidence: 99%